HUBUNGAN FILSAFAT ILMU DENGAN FILSAFAT HUKUM DAN DAMPAK KEMAJUAN TEKNOLOGI INFORMASI - Musa Musa; Surajiman Surajiman (INTELIGENSIA MEDIA, 2023)
On the one hand, the philosophy of science can be used as a basis for making legal theory. In this case, legal theory is deliberately designed to be more applicable and able to answer questions of justice in society. Philosophy of science can be the basis for contemplation or thinking strictly, in depth about considering the values behind legal phenomena as can be observed by human senses regarding human actions and social habits. Considering that the object of the philosophy of science is knowledge, the problems or questions discussed by the philosophy of science are related to the benefits of knowledge itself.